Allelopathic effects of aqueous extract of Brassica napus on germination of seeds of Phaseolus vulgaris - Rigon, João P. G. [UNESP]; Capuani, Silvia [UNESP]; Cherubin, Maurício R.; Wastowski, Arci D.; Da Rosa, Genesio M. (Revista Brasileira de Ciencias Agrarias, 2012)
Secondary compounds produced by plants are considered an alternative method of weed suppression but can cause negative effects on crops in succession, especially in a no-tillage system, due to the degradation of crop residues with allelopathic potential. The objective of this work was to analyze the influence of foliar aqueous extracts of Brassica napus on the germination and initial development of seedlings of Phaseolus vulgaris. The extract was prepared as a stock 10 % weight/volume solution, and diluted into treatments of relative concentrations of 100 % (i.e. 10 % w/v stock), 75 %, 50 %, 25 % and 0 % (untreated control consisting of distilled water), in a completely randomized design. The seeds of Phaseolus vulgaris were moistened with the differing concentrated extracts and kept in a germination chamber at 25 °C, with a photoperiod of 12 h for nine days. The variables evaluated were: percentage germinating, first count of germination and germination velocity index, as well the root and hypocotyl length, and fresh and dry mass of the seedlings. The aqueous leaf extracts of Brassica napus did not influence the germination of Phaseolus vulgaris seeds, but did induce the growth of abnormal seedlings by inhibition of secondary roots and reduced prominence of the primary root.
Keywords: Allelochemicals; Crop succession; Development of seedlings; Brassica napus; Phaseolus vulgaris